Shp2 signaling suppresses senescence in PyMT‐induced mammary gland cancer in mice. (14th September 2015) - Lan, Linxiang; Holland, Jane D; Qi, Jingjing; Grosskopf, Stefanie; Vogel, Regina; Györffy, Balázs; Wulf‐Goldenberg, Annika; Birchmeier, Walter
Abstract :